MARKETING STRATEGY OF PETROKIMIA GRESIK NON-SUBSIDIZED NPK FERTILIZER TO WIN MARKET COMPETITION - Barra Selabean Sasiwou (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
PT Petrokimia Gresik is faced with a very fast changing business environment (turbulence). The global economic slowdown coupled with a decline in international commodity prices led to lower prices for imported fertilizers. The government began decreasing the amount of subsidized fertilizer each year. This reduction in allocation is a warning that the government will completely revoke the fertilizer subsidy. With the reduction in subsidies, there will be a potential non-subsidized NPK market, thereby attracting the interest of competitors in the private sector. Changes in the business environment provide opportunities as well as threats for PT Petrokimia Gresik to realize its vision. The study uses internal and external analysis to identify the factors that have the most potential to influence the achievement of company goals. The research explores information directly from sources using the interview method (in-depth interview). This study aims to find the company's strategic position according to the internal external (IE) matrix concept and provide recommendations for strategy formulation with the diamond concept. The results showed that the strategic position of PT Petrokimia Gresik was hold and maintain. The strategy that can be developed by the company is an intensive strategy, namely developing existing products and developing markets by penetrating the market into the plantation sector. In addition, the company's business strategy was formulated based on the concept of a diamond strategy including arena, vehicle, differentiators, staging, and economic of logic.